Atomoxetine treatment and ADHD-related difficulties as assessed by adolescent patients, their parents and physicians - Lehmann Martin; Minarzyk Anette; Schacht Alexander; Wehmeier Peter M; Dittmann Ralf W; Sevecke Kathrin; Lehmkuhl Gerd (BMC, 2009)
Abstract Background The degree of ADHD-related difficulties - reflecting overall impairment, social functioning, and quality of life - may be perceived differently by adolescent patients, parents and physicians. The primary aim of this study was to investigate ADHD-related difficulties during atomoxetine treatment, as perceived by the three different raters. Secondary objectives focused on effectiveness and tolerability of atomoxetine treatment in a population of adolescent patients with ADHD. Methods Adolescents with ADHD, aged 12-17 years, received open-label atomoxetine (0.5-1.2 mg/kg/day) up to 24 weeks. ADHD-related difficulties at various times of the day were rated using the Global Impression of Perceived Difficulties (GIPD) instrument. Inter-rater agreement was analyzed using Cohen's Kappa with 95% confidence intervals (95% CI). ADHD-Rating Scale (ADHD-RS) and Clinical Global Impression Severity (GGI-S) scores were assessed by the investigator; and spontaneous adverse events, vital signs and laboratory parameters were collected for tolerability assessments. Results 159 patients received atomoxetine. Patients' baseline mean GIPD total ratings were significantly lower than parents' and physicians' scores (12.5 [95%CI 11.6;13.5] vs. 17.2 [16.2;18.2] and 18.8 [17.8;19.8]). For all raters, GIPD scores significantly improved over time. Changes were greatest within the first two weeks. Kappa coefficients varied between 0.186 [0.112;0.259] and 0.662 [0.529;0.795], with strongest agreements between parent and physician assessments, and significant improvements of patient/physician agreements over time (based on 95% CIs). ADHD-RS and CGI-S scores significantly improved over the course of the study (based on 95% CIs). Tolerability results were consistent with earlier reports. Conclusion ADHD-related difficulties were perceived differently by the raters in this open-label trial, but consistently improved during atomoxetine treatment. The GIPD instrument appeared sensitive to treatment-related change. These primarily quantitative findings may guide future studies to more systematically investigate the clinical and practical relevance of the differences observed. Additionally, in order to further validate these results, placebo- and comparator-controlled trials are recommended as well as inclusion of healthy controls and other patient populations. Trial Registration Clinical Trial Registry: ClinicalTrials.gov: NCT00191737